2016
DOI: 10.1530/jme-16-0033
|View full text |Cite
|
Sign up to set email alerts
|

60 YEARS OF POMC: Lipotropin and beta-endorphin: a perspective

Abstract: Many important fields of research had a humble origin. In the distant past, A J P Martin's discovery that amino acids could be separated by paper chromatography and Moore and Stein's use of columns for quantitative amino acid analysis provided the first steps towards the determination of structure in complex biologically active molecules. They opened the door to reveal the essential relationship that exists between structure and function. In molecular endocrinology, for example, striking advances have been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
2
17
0
6
Order By: Relevance
“…A previous observational study investigated the decrease in β‐EP in opioid addiction models, especially in the blood, spinal cord, and brain nuclei . Our previous work and that of others confirmed that upregulation of exogenous β‐EP could attenuate withdrawal syndrome in opioid‐dependent rats . Moreover, studies have shown that glycyl‐glutamine, DTgammaE, and DEgammaE, which are the active peptide and fragments derived from β‐EP, respectively, present favorable effects on attenuation of opioid withdrawal symptoms .…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…A previous observational study investigated the decrease in β‐EP in opioid addiction models, especially in the blood, spinal cord, and brain nuclei . Our previous work and that of others confirmed that upregulation of exogenous β‐EP could attenuate withdrawal syndrome in opioid‐dependent rats . Moreover, studies have shown that glycyl‐glutamine, DTgammaE, and DEgammaE, which are the active peptide and fragments derived from β‐EP, respectively, present favorable effects on attenuation of opioid withdrawal symptoms .…”
Section: Introductionsupporting
confidence: 69%
“…12,13 Our previous work and that of others confirmed that upregulation of exogenous β-EP could attenuate withdrawal syndrome in opioiddependent rats. [14][15][16][17] Moreover, studies have shown that glycylglutamine, DTgammaE, and DEgammaE, which are the active peptide and fragments derived from β-EP, respectively, present favorable effects on attenuation of opioid withdrawal symptoms. 11,18 This evidence strongly indicates that β-EP plays an important role in preventing opioid addiction.…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to its sequence, which confers resistance to degradation. There is also the suggestion that the more COOH-terminal region of ␤-endorphin acts in "an address function," by presenting the peptide to the receptor to aid specificity and potency (378). This could be considered another advantage of the presence of a peptide within a larger pro-hormone structure.…”
Section: The Opiate Activity Of ␤-Endorphinmentioning
confidence: 99%
“…An equivalent peptide had not been identified in extracts of murine pituitary glands, but a β-MSH-like peptide with a four-amino acid N-terminal extension (Ala-Glu-Lys-Lys) had been isolated from human pituitaries extracted at mild pH (Dixon 1960). In those mammals in which the primary structure of β-lipotrophin (β-LPH) was elucidated, it was revealed that they all contained the sequence of their appropriate β-MSHs (banded by double basic amino acids: Lys-Arg or Arg-Arg), and thus, it was naturally assumed that β-LPH could be the precursor of β-MSH by simple proteolytic processing at the double basic residues by trypsin-like activity (Chretien & Mbikay 2016, Smyth 2016. The situation with human β-MSH was atypical, as it appeared not to be cleaved from its β-LPH at the N-terminal Lys-Lys double basic motif but in a non-trypsin-like manner at an Ala-Ala peptide bond.…”
Section: Mammalian β-Mshmentioning
confidence: 99%